Effects of TiF3 addition on the hydrogen storage properties of 4MgH2 + Cd composite. (22nd November 2019) - Sulaiman, N.N.; Ismail, M.
Abstract: In this paper, the best performance of the MgH2 destabilized system with different ratios of Cd (1:1, 2:1, 3:1 and 4:1) have been studied for the first time. Remarkable enhancements on the onset dehydrogenation temperature, as well as the isothermal de/rehydrogenation kinetics were shown by the 4MgH2 + Cd composite. In order to improve the hydrogen storage properties of the 4MgH2 + Cd, TiF3 was added and its catalytic effects were investigated. Temperature programmed dehydrogenation result had revealed that the onset dehydrogenation temperature was improved once the 10 wt% TiF3 was incorporated into the 4MgH2 + Cd system. The absorption and desorption kinetics were also improved compared to the un-doped 4MgH2 + Cd composite system. The scanning electron microscope result had displayed that the 4MgH2 + Cd + 10 wt% TiF3 had the smallest particle size compared to the pure and the ball-milled MgH2, as well as the 4MgH2 + Cd composite system. The X-ray diffraction results had demonstrated the formation of an intermediate compound, Mg3 Cd, which was formed during the heating process. For the TiF3 -doped sample, it is reasonable to conclude that the in - situ formed TiH2 and F-containing species play a synergetic role to encourage interactions between the MgH2 and the Cd and thus further ameliorate the performances of the hydrogen storage of 4MgH2 + Cd composite system. Highlights: The H2 storage properties of MgH2 /CdTiF3 have been studied for the first time. Sorption properties of MgH2 /Cd are improved after adding with TiF3. EA for hydrogen desorption of doped composite was lowered to 107.0 kJ/mol. The in - situ formation of the TiH2 and F-containing species play a synergetic role.